KAJIAN PEMIKIRAN YUSUF QARDHAWI TENTANG PENGENTASAN KEMISKINAN - Muhammad Amri Robbani; Muttaqin, Aminullah Achmad (Islamic Economics and finance in Focus, 2023)
This study aims to find out Yusuf Qardhawi's thoughts on the concept of poverty alleviation. The researcher used the library research method in examining Yusuf Qardhawi's thoughts on poverty alleviation through a book written by Yusuf Qardhawi entitled Musykilat al Faqri wa Kaifa Alajaha al Islam which was translated by Syafril Halim along with Yusuf Qardhawi's other books and journals as support. The results of this study indicate that the concept of poverty alleviation put forward by Yusuf Qardhawi is based on Islamic teachings that poverty can be overcome by working, family compensation, zakat and non-zakat assistance with a note that the concept of Islamic teachings is fully implemented.